Referrals from general practice to consultants in Germany: If the GP is the initiator, patients' experiences are more positive - Wensing Michel; Rosemann Thomas; Rueter Gernot; Szecsenyi Joachim (BMC, 2006)
Abstract Background Referrals of patients from primary care to medical specialist care are an important activity in any health care system. German data show that the number of referrals by GPs have increased since 2004, but detailed insight into the experiences of patients, GPs and consultants regarding referrals is very limited. This study aimed at describing the experiences of consultants, GPs and patients with referrals from primary care to medical specialist care. An additional objective was to examine the impact of purpose regarding the referral and of the referrer on the experiences of GPs and patients. Methods Referrals of 26 general practitioners (GPs) from 25 practices in Marbach, a rural region in the south of Germany were studied. All adult patients referred after consulting these GPs in a period of five weeks were eligable for the study. GPs, consultants and patients completed short structured forms to document factual characteristics of each referral and their experiences with the referral. GPs and patients completed forms before and after the referral was made, while the consultants completed forms after the patient had consulted them. Results Overall, consultants were very positive about appropriateness of the referral (91%). They were somewhat more critical regarding the information provided on the patients' medical history (61%) and prescriptions (48%). In 258 referrals (63%) GPs perceived clear diagnostic benefits, while in 202 referrals (49%) they perceived clear treatment benefits. GPs' experiences were more positive if the GP's purpose was to reduce diagnostic uncertainty (beta = 0.318, p < 0.001) or if the purpose was to exclude serious illness (beta = 0.143, p < 0.010). Other purposes of the referral had no impact on their experiences. Patients' expectations regarding the referrals mostly referred to diagnosis, including increased diagnostic certainty (80%), detailed information about the illness (66%) and exclusion of serious illness (62%). They were overall satisfied with the referral (83%). Their experiences with the referral were more positive if the initiative for the referral came from the physician (beta = 0.365, p < 0.000). Conclusion Patients, GPs and consultants have positive views on the value of referrals from primary care to medical specialists. Patients were most positive if the physician had initiated the referral, which supports the gate keeper role of the GP.